Development of groundwater quality index for non-potable use via proportional technique - Haspi Harun, Hazimah (2021)
Groundwater resources have also been used for many years in other countries such as India, Saudi Arabia, the United Kingdom, and the Netherlands. Furthermore, groundwater resources have long been used in several states in Malaysia, for example in Kelantan, Kedah, and Terengganu and several parts in remote areas that have difficulty getting the tap water supply and nearby the coastal areas such as Sabah and Sarawak. The development of the groundwater quality index (GWQI) in this study is vital as the groundwater is considered an alternative water source for non-potable use. The inadequacy of Malaysia's groundwater quality standard highlighted the importance of the GWQI's development in determining groundwater quality. The aim of this study was to develop a GWQI that represents the water quality data as a single number to present the quality of groundwater. This study was focusing the groundwater sources in the agricultural areas because it is believed that many wells were excavated for irrigation purposes in agricultural areas. The groundwater samples were collected from 13 groundwater wells in the Northern and Southern Kuala Langat regions from February 2018 to January 2019. A total of 34 parameters have been identified for the development of the GWQI such as salinity, pH, nitrate, BOD, COD, major ions, and trace elements. Statistical analysis was conducted to identify the dominant parameters in the GWQI. From the Principal Component Analysis (PCA), seven parameters have been identified as dominant parameters, which were magnesium, calcium, potassium, sodium, chloride, electrical conductivity, and chemical oxygen demand which were suitable to determine the quality of groundwater. This study found that the GWQI in Kuala Langat, Selangor shows a value of 64 which is classified as good quality. This GWQI has also been verified by measuring the quality of groundwater in Kota Bharu, Kelantan, which has similar features to the current study in terms of agricultural activity and proximity to coastal areas. Therefore, the GWQI shows an excellent index value of 96 which the groundwater in Kota Bharu, Kelantan is very clean and suitable for use as non-potable water utilization. GWQI has also been tested for sensitivity analysis to determine its reliability and suitability to be used and assess the quality of groundwater in other areas. This study contributes to new knowledge by determining the quality of groundwater for non-potable use, filling a gap in the study for groundwater exploitation. Furthermore, unlike the GWQI introduced by DOE Malaysia, which included parameters such as pH, iron, dissolved solids, nitrate, sulfate, phenol, and E. coli, this index does not include parameters needed for drinking purposes. However, the parameter from major ions, electrical conductivity, and COD was disclosed to the GWQI in this study to estimate the quality of groundwater for non-potable usage. As a result, the findings of this study are innovative, as a suitable GWQI has been created to determine groundwater quality, particularly for non-potable applications. This GWQI is beneficial to the community, practitioners, researchers, policymakers, industrial sectors, and government agencies. Furthermore, this index can help to detect any form of pollution and the pollution can be reduced by controlling the source of pollutants. As a recommendation for future studies, this GWQI requires a detailed health assessment and considered the important parameters for drinking water supply as recommended by the Ministry of Health whether it is safe for human health.